Factors employee loyalty in organization / Fateen Nazirah Jamsari and Siti Nurulain Hashim - Jamsari, Fateen Nazirah; Hashim, Siti Nurulain (Faculty of Business and Management, 2013)
Organization nowadays facing high competition. They need to provide best benefits to their employee in order to make they stay longer in their organization. No matter what type of industry, every organization will give benefits to their employee as recognition. By doing this, it can make the employee stay longer in the organization or in short they will be employee loyalty. Employee loyalty can be defined as employees being committed to the success of the organization and believing that working for this organization is their best option. They play vital role for the organization improvement. However, it is not easy to maintain the employee loyalty in an organization. There are several variables that influence the employee loyalty in the area of Shah Alam. There are employee motivation, compensation and rewards, job security, and workplace environment. Based on the four variables stated above, we conducting this research as the aim of the study is to find the factors that contribute employee loyalty in the organization in area of Shah Alam. This study also is to find whether the four variables have relationship between the employee loyalty. From this research, there are some evidence which can prove the reliability to the four variables as mentioned earlier. Thus, an organization need to focus more on employee motivation, compensation and rewards, job security, and workplace environment in order to make their employee become loyalty. In order to achieve the aim of study, questionnaire survey was used for this research project. The researcher had contributed the questionnaire to the employees who worked in the organization in area of Shah Alam. This will help the researcher to obtain accurate variable. Besides that, this research also will define the most reliable factors that contribute to employee loyalty. Apart from that, this research also has several recommendations as proposed in the last part of this research as it could generate employee loyalty in the organization in the area of Shah Alam. By recommendation, it could enhance the company profitability and operation.